PjBL-Based Blended Learning Implementation on Energy Topic to Improve the Problem-Solving Skill - Gestira, Mega; Abdurrahman; Viyanti (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2021)
Blended learning is a new strategy or way in the learning process. Besides face-to-face learning, the learning process should also be carried out in an online manner. Online learning could facilitate teachers and learners to learn anywhere and anytime. It is an appropriate learning strategy and supported by a learning model that could integrate various science disciplines, such as science, technology, engineering, and mathematics. This research aims to describe the improvement of problem-solving skills on energy via blended learning-based PjBL STEM. Each syntax of the learning consists of five-stage. They are problem solving, focus the problem, describe the problem in physics description, plan a solution, execute the plan, and evaluate the solution. This research applied an experimental research design with pre-experimental (one group pretest-posttest design). The sample consisted of thirty-five Al-Azhar Islamic SHS 3 Bandar Lampung at X Science 1. The instrument was a problem-solving skill test in the form of an essay. The test results were analyzed with paired sample t-test. Based on the promoted research, the N-gain of experimental group learning outcome was 0.43, categorized moderate. The paired sample t-test hypothesis result obtained the Asymp. Sig (2-tailed) ≤0,05 is 0,00. It showed the improvement of problem-solving skills using the blended-learning-based PjBL STEM model.